Evaluation of open and minimally invasive adrenalectomy: a systematic review and network meta-analysis - Heger, Patrick; Probst, Pascal; Hüttner, Felix; Goossen, Käthe; Proctor, Tanja; Müller, Beat P.; Strobel, Oliver; Büchler, Markus W.; Diener, Markus K. (World journal of surgery, 2017)
Background Adrenalectomy can be performed via open and various minimally invasive approaches. The aim of this systematic review was to summarize the current evidence on surgical techniques of adrenalectomy. Methods Systematic literature searches (MEDLINE, EMBASE, Web of Science, Cochrane Library) were conducted to identify randomized controlled trials (RCTs) and controlled clinical trials (CCTs) comparing at least two surgical procedures for adrenalectomy. Statistical analyses were performed, and meta-analyses were conducted. Furthermore, an indirect comparison of RCTs and a network meta-analysis of CCTs were carried out for each outcome.Results Twenty-six trials (1710 patients) were included. Postoperative complication rates did not show differences for open and minimally invasive techniques. Operation time was signiﬁcantly shorter for open adrenalectomy than for the robotic approach (p \ 0.001). No differences were found between laparoscopic and robotic approaches. Network meta-analysis showed open adrenalectomy to be the fastest technique. Blood loss was signiﬁcantly reduced in the robotic arm compared with open and laparoscopic adrenalectomy (p = 0.01). Length of hospital stay (LOS) was signiﬁcantly lower after conventional laparoscopy than open adrenalectomy in CCTs (p \ 0.001). Furthermore, both retroperitoneoscopic (p \ 0.001) and robotic access (p \ 0.001) led to another signiﬁcant reduction of LOS compared with conventional laparoscopy. This difference was not consistent in RCTs. Network meta-analysis revealed the lowest LOS after retroperitoneoscopic adrenalectomy. Conclusion Minimally invasive adrenalectomy is safe and should be preferred over open adrenalectomy due to shorter LOS, lower blood loss, and equivalent complication rates. The retroperitoneoscopic access features the shortest LOS and operating time. Further high-quality RCTs are warranted, especially to compare the posterior retroperitoneoscopic and the transperitoneal robotic approach.
Published online: 20 June 2017
Gesehen am 24.10.2018